2017
DOI: 10.1002/hyp.11227
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation and the subcanopy energy environment in a flooded forest

Abstract: The combination of tree canopy cover and a free water surface makes the subcanopy environment of flooded forested wetlands unlike other aquatic or terrestrial systems. Subcanopy vapour fluxes and energy budgets represent key controls on water level and understorey climate but are not well understood. In a permanently flooded forest in south‐eastern Louisiana, USA, an energy balance approach was used to address (a) whether evaporation from floodwater under a forest canopy is solely energy limited and (b) how en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…As a whole, the cumulative annual sums of half‐hourly G w at YX were negative, indicating a net release of stored tidal water heat energy to the mangrove ecosystem, while cumulative values at the GQ and LZ mangrove ecosystems were positive. The main difference in G w terms between the GQ and YX ecosystems happened in autumn and winter when values of G w were largest but other components of the surface energy budget were relatively small, consistent with the observations of Allen et al () and Shoemaker et al (). Our addition of G w into equation improved energy balance closure in the three mangrove ecosystems by 2% to 3%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As a whole, the cumulative annual sums of half‐hourly G w at YX were negative, indicating a net release of stored tidal water heat energy to the mangrove ecosystem, while cumulative values at the GQ and LZ mangrove ecosystems were positive. The main difference in G w terms between the GQ and YX ecosystems happened in autumn and winter when values of G w were largest but other components of the surface energy budget were relatively small, consistent with the observations of Allen et al () and Shoemaker et al (). Our addition of G w into equation improved energy balance closure in the three mangrove ecosystems by 2% to 3%.…”
Section: Discussionsupporting
confidence: 89%
“…First, one of the most important differences between mangrove ecosystems and fully terrestrial ecosystems is the impact of tidal fluctuations, as enthalpy exchange with tidal waters (G w ) may affect closure of the surface energy balance as indicated by equation ( 7) (Sobrado, 2007;. Allen et al (2017) and Shoemaker et al (2005) also found that the contributions of vertical exchange with surface water were an essential component of the surface energy budget in wetlands, particularly on dry winter days when surface energy exchanges were seasonally weak. Contributions of tidal water (G w ) to the surface energy budget consist of (1) vertical exchange between the tidal water and the air above or soil below (i.e., the net heating of surface water) and ( 2) lateral transport during ebb-and-flood tides (G adv ).…”
Section: Adjustments To the Two-source Model For Mangrove Ecosystemsmentioning
confidence: 99%
“…Vegetation structure can further influence ET through effects to energy partitioning. For instance, canopy structure filters energy inputs for understory transpiration and direct evaporation of standing and/or soil water (Allen et al, 2017). Additionally, canopy structure likely influences snowfall interception and sublimation and wind redistribution that can result in less snow pack under ash relative to clearcut treatments (Molotch et al, 2007;LaMalfa and Ryle, 2008;Veatch et al, 2009).…”
Section: Ecohydrologic Controlsmentioning
confidence: 99%
“…Under inundated conditions (defined throughout as water level > 0), open water evaporation can become an additional and dominant ET component, often exceeding transpiration rates (Allen, Reba, Edwards, & Keim, 2017). Our previous work in lowland flats suggests that this water level control may determine the extent of ET reduction following tree mortality.…”
Section: Introductionmentioning
confidence: 97%